Restoring degraded forests and agricultural landscapes in the Gambia through policies to implement eco-based adaptation systems and interventions that aim to restore 7,000 ha of degraded forests and 3,000 ha agricultural land, with 11,550 and 46,200 direct and indirect beneficiaries respectively - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
With ICRAF support, the Gambia adopts the Banjul Tree Cover Resolution and the he Banjul Multi-sectoral Integrated Livestock Management Resolution paving the way towards a sustainable green economy based on climate-resilient livelihoods and rigorous, evidence-based management of natural resources.